PENGARUH PEMBERDAYAAN PEGAWAI TERHADAP KINERJA ORGANISASI KANTOR KECAMATAN HARUYAN KABUPATEN HULU SUNGAI TENGAH - Erna Suriyani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The purpose of this study is to determine the effect of empowerment of employees on organizational performance at the District Office Haruyan Hulu Sungai Tengah. The type of research used is explanatory, while the research approach is a quantitative approach.The findings of research that is at a significant level of 5% proved to have an effect of empowerment of employees who viewed from the desire to the performance of Haruyan District Office, while for 1% it turned out that the empowerment of pegawi does not affect the performance of the organization. At a significant level of 5% proved to have an effect of employee empowerment viewed from trust to organizational performance, while for 1% no effect. At a significant level of 5% proved to have an effect variable employee empowerment seen from confident to the performance of the organization, while 1% no effect. And there is influence empowering employees seen from the cridibility of organizational performance at a significant level of 5%, while at 1% no effect. At a significant level of 1% and 5% proved to have an effect of employee empowerment seen from accountability to organizational performance. And at a significant level of 5% proved to have an effect of empowering employees viewed from comunication to organizational performance, while at 1% no effect.